PEMBELAJARAN MEMBACA TEKS DESKRIPSI MELALUI PENDEKATAN SAINTIFIK DENGAN MODEL PROBLEM BASED LEARNING (PBL) PADA SISWA SMP NEGERI 6 SUBANG - Julianto Julianto (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2019)
Reading is receptive or accepting activity. The reading activity of some students is considered not a necessity or a necessity. In fact, reading activities need to be taught or familiarized as early as possible. The ability to read does not come alone, suddenly, or just come, but requires a process of practice or practice continuously, and has a clear purpose. A person who has good reading skills will think critically and have good understanding. The obstacles experienced by students in reading are students who consider reading trivial or trivial things. Then, students only carelessly read or did not have a clear purpose. There are several causes of low student reading ability, namely the lack of examples or exemplary parents or teachers in reading books, lack of reading material, environmental factors, and effective education strategies or reading techniques. Learning in the 2013 curriculum implements a scientific approach. The scientific approach is an approach that focuses on science, facts, phenomena, and context. Some learning models that use a scientific approach such as discovery learning, project based learning, problem based learning, and inquiry learning. In optimizing reading learning requires an effective approach or model. One of them is the scientific approach with a problem based learning model. The problem based learning model requires students to think critically in solving problems in both learning and everyday life. The research design used in this study used a pre-experimental design with type one group pretest posttest design. In the application of the one-group pretest-posttest design there is the application of pretest or initial test before treatment and posttest or test given treatment with a problem based learning model. Then, the results before and after given treatment are compared to find out the effectiveness of the problem based learning model in learning to read the description text in class VII-E students of SMP Negeri 6 Subang. Stages of statistical calculations start from searching for the average value, normality test, homogeneity test, and hypothesis testing. The average pretest is 53.3, while the posttest average value is 73.1. From the results of the average value before and after it can be compared that there is a difference in value of 19.8. The normality test is known that the pretest significance value is 0.200, while for the posttest value is 0.200. The homogeneity test can be seen from the significance value of the pretest and posttest is 0.342. Hypothesis testing the significance value of pretest and posttest is 0,000. So, there is a difference between the average test scores before and after being treated with a competitive approach with the problem based learning model in reading the description text.